Regards croisés autour de la légitimation de la catégorie « agriculture familiale » et ses défis conceptuels - Clara Craviotti (Bulletin de l’Association de Géographes Français)
Family agriculture as a political category spreads in Latin America from the early 2000s. There was a particularly strong influence of the international field, visible in both the circulation of ideas and the political agreements reached between the governments of several countries of the region. This article adopts a comparative perspective, taking into account how certain models of family agriculture took shape in the policies of the French state, were later incorporated into the initiatives developed in Brazil and have been appropriated by other Southern Cone countries such as Argentina, paying attention to the specific contexts in which these initiatives were produced. The central argument is that during this process a broader definition of family farming is affirmed with certain political legitimation, but it also causes some discomfort from a conceptual point of view, because it limits the visibility of the heterogeneity of agents included by the category. Some analytical axes that can be used to identify its diversity are thus presented, in order to understand current expressions of family farming and its trends of change.